Financial evolution of the Caribbean Community (1970-1996) - Clarke, Laurence ed. (Caribbean Centre for Monetary Studies St. AugustineTT, 1997)
Documents the post-independence financial history of the Caribbean Community and Nation. Provides a detailed chronology of the evolution of the financial institutions and economies of the Bahamas, Barbados, Belize, Eastern Caribbean States, Guyana, Jamaica, Suriname and Trinidad and Tobago.